Measurement of τ polarisation in Z / γ ∗ → τ τ decays in proton-proton collisions at s = 8 TeV with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Abdinov, O; Abeloos, B; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al. (The European physical journal. C, Particles and fields, 2018)
This paper presents a measurement of the polarisation of τ leptons produced in Z / γ ∗ → τ τ decays which is performed with a dataset of proton-proton collisions at s = 8 TeV, corresponding to an integrated luminosity of 20.2 fb - 1 recorded with the ATLAS detector at the LHC in 2012. The Z / γ ∗ → τ τ decays are reconstructed from a hadronically decaying τ lepton with a single charged particle in the final state, accompanied by a τ lepton that decays leptonically. The τ polarisation is inferred from the relative fraction of energy carried by charged and neutral hadrons in the hadronic τ decays. The polarisation is measured in a fiducial region that corresponds to the kinematic region accessible to this analysis. The τ polarisation extracted over the full phase space within the Z / γ ∗ mass range of 66 < m Z / γ ∗ < 116 GeV is found to be P τ = - 0.14 ± 0.02 ( stat ) ± 0.04 ( syst ) . It is in agreement with the Standard Model prediction of P τ = - 0.1517 ± 0.0019 , which is obtained from the ALPGEN event generator interfaced with the PYTHIA 6 parton shower modelling and the TAUOLA τ decay library.